A comparison of system performance using two different chip pulses in multiple-chip-rate DS - Young Woo Kim (IEEE Transactions on communications)
This paper describes a comparison of system performance using two different chip waveforms of spreading sequences in multiple-chip-rate (MCR) direct-sequence (DS)/code-division multiple-access (CDMA) systems. The chip pulses used in this study are closely related to the characteristics of output filter employed at transmitter. In general, the chip waveform is an important factor to determine the link performance. The raised cosine chip pulse with a roll-off factor of α will be adopted for IMT-2000 systems in order to reduce both the intersymbol effect and the spectral width of the modulated signal. However, due to the complexity of obtaining quantitative results on the performance of MCR-DS/CDMA systems, rectangular chip pulses are mainly utilized in performance analysis. Therefore, it is necessary to investigate the effect of the chip pulses used, i.e., a rectangular and a raised cosine chip pulses on system performance in order to evaluate MCR-DS/CDMA systems accurately. Thus, the effect of the chip pulses used on the performance in MCR-DS/CDMA systems is investigated in terms of the system capacity and blocking probability. It is shown that the system using a raised cosine chip pulse (i.e., RC system) supports at least 80% more capacity and 57% more traffic than that using a rectangular chip pulse (i.e., R system)